Toward The Highest Morality Of The Human Soul: A Study Of The Concept Fana Abdullah Al-Ansari Al-Harawi and Nibbana In Buddha - Farobi, Ahmad (Studi Multidisipliner: Jurnal Kajian Keislaman, 2024)
The term Fana' in Sufism is the elimination of all forms of lust and despicable traits in human beings, this has similarities with the concept of Nibbana found in Buddhism, Nibbana is achieved through the practice of curbing greed, hatred and avarice. This research aims to explain the relevance of the teachings of Fana' from the perspective of Abu Abdullah Al-Harawi and Nibbana according to Buddhism. The method in this research is qualitative analytical with the primary source being the book Manazil al-Sairin and secondary sources in the form of journals and books that are still relevant to the research topic. This discussion explains the meaning of Fana' in Sufism according to Al-harawi and the meaning of Nibbana according to Buddha and the relevance of both. This research has implications for understanding the concept of teachings that deal with aspects of personal purity from the perspective of different religions, namely Islam and Buddhism. The results of this research explain that both teachings emphasize the aspect of purifying the human soul from all despicable traits, according to al-Harawi Fana is not eliminating the form of something that has been embedded in the soul or body, because the mind and body are one unit and are able to receive the nature of Haqq's existence, then fana' will not be formed without deepening ma'rifah. In Buddhism, a person reaches Nibbana when he has escaped the bonds of the world in all its aspects, so that a person feels a spiritual satisfaction that he experiences. Therefore, between Fana according to Al-Harawi and Nibbana according to Buddha, both have a concept towards the culmination of the highest moral teachings of the human soul, because both provide the conclusion of separation from the worldly life.